2009 International Conference for Internet Technology and Secured Transactions, (ICITST) 2009
DOI: 10.1109/icitst.2009.5402542
|View full text |Cite
|
Sign up to set email alerts
|

On the fractal characteristics of Internet network traffic and its utilization in covert communications

Abstract: There are many models in the literature that consider the main characteristics of Internet traffic either by processing the real measurements of traffic in the time-or frequencydomain. In this paper we use the latter approach and introduce a novel method to capture the fractal behavior of Internet traffic in which we adopt a random scaling fractal model to simulate the self-affine characteristics of the Internet traffic. In this paper we utilize the self-affine nature of Internet traffic in order to disguise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…One possible goal for developers is to build a unified high-speed communication network platform capable of carrying diverse traffic and supporting diverse levels of Quality of Service (QoS). Recent studies of real telecommunications network traffic data have shown that teletraffic exhibits self-similar (or fractal) properties over a wide range of time scales (Boxma & Cohen, 2000;Marie, Blackledge, & Bez, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One possible goal for developers is to build a unified high-speed communication network platform capable of carrying diverse traffic and supporting diverse levels of Quality of Service (QoS). Recent studies of real telecommunications network traffic data have shown that teletraffic exhibits self-similar (or fractal) properties over a wide range of time scales (Boxma & Cohen, 2000;Marie, Blackledge, & Bez, 2007).…”
Section: Introductionmentioning
confidence: 99%